Analysis of the Monte Carlo Method in Simulation of Snake and Ladder Game Using R Programming - Afif Yasri; Ramlan Marbun; Harefa, Ade May Luky; Muhammad Syahputra Novelan (SEAN Institute, 2025)
This study applies the Monte Carlo method to simulate the classic board game